2015
DOI: 10.1002/dvg.22884
|View full text |Cite
|
Sign up to set email alerts
|

BAC transgenic zebrafish reveal hypothalamic enhancer activity around obesity associated SNP rs9939609 within the human FTO gene

Abstract: SummarySingle Nucleotide Polymorphisms in FTO intron 1 have been associated with obesity risk, leading to the hypothesis that FTO is the obesity‐related gene. However, other studies have shown that the FTO gene is part of the regulatory domain of the neighboring IRX3 gene and that enhancers in FTO intron 1 regulate IRX3. While Irx3 activity was shown to be necessary in the hypothalamus for the metabolic function of Irx3 in mouse, no enhancers with hypothalamic activity have been demonstrated in the risk‐associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In the same study, in vivo promoter probing in mice of the FTO proximal promoter, and the FTO proximal promoter plus the FTO obesity‐associated intronic region, showed comparable reporter expression, whereas promoter probing of the IRX3 proximal promoter did not show any expression patterns. These results, and similar studies in zebrafish, 57 suggest that distinct enhancer elements are required for IRX3 expression but not for FTO . FTO and RPGRIP1L expression is ubiquitous but regulated by nutritional state in the hypothalamus 18,58 .…”
Section: Electrophoretic Mobility Shift Assays (Emsa) and Promoter Pr...supporting
confidence: 75%
“…In the same study, in vivo promoter probing in mice of the FTO proximal promoter, and the FTO proximal promoter plus the FTO obesity‐associated intronic region, showed comparable reporter expression, whereas promoter probing of the IRX3 proximal promoter did not show any expression patterns. These results, and similar studies in zebrafish, 57 suggest that distinct enhancer elements are required for IRX3 expression but not for FTO . FTO and RPGRIP1L expression is ubiquitous but regulated by nutritional state in the hypothalamus 18,58 .…”
Section: Electrophoretic Mobility Shift Assays (Emsa) and Promoter Pr...supporting
confidence: 75%
“…The function of rs4646536 is unknown. It has been reported that gene expression could be influenced by variants in intron via affecting the binding of transcription factors and splicing of mRNA . Thus, allele variation of rs4646536 from C to T may result in abnormal expression of CYP27B1 , which would lead to disorder of 25(OH)D concentration.…”
Section: Discussionmentioning
confidence: 99%
“…3 ). In addition, studies have found that the FTO promoter does not respond to long-range regulation during zebrafish development ( Rinkwitz et al, 2015 ). Recently, it has been shown that rs1421085 is located within an ARID5B binding site, leading to impaired ARID5B -mediated repression of IRX3 and IRX5 during early adipocyte differentiation ( Claussnitzer et al, 2015 ).…”
Section: Studies Of Individual Loci Illuminate the Fallacy Of Nearest...mentioning
confidence: 99%